Idiopathic multicentric Castleman's disease: a systematic literature review. Issue 4 (April 2016) - Liu, Amy Y; Nabel, Christopher S; Finkelman, Brian S; Ruth, Jason R; Kurzrock, Razelle; van Rhee, Frits; Krymskaya, Vera P; Kelleher, Dermot; Rubenstein, Arthur H; Fajgenbaum, David C
Summary: Background: Multicentric Castleman's disease describes a group of poorly understood lymphoproliferative disorders driven by proinflammatory hypercytokinaemia. Patients have heterogeneous clinical features, characteristic lymph node histopathology, and often deadly multiple organ dysfunction. Human herpesvirus 8 (HHV8) causes multicentric Castleman's disease in immunosuppressed patients. The cause of HHV8-negative multicentric Castleman's disease is idiopathic; such cases are called idiopathic multicentric Castleman's disease. An absence of centralised information about idiopathic multicentric Castleman's disease represents a major challenge for clinicians and researchers. We aimed to characterise clinical features of, treatments for, and outcomes of idiopathic multicentric Castleman's disease. Methods: We did a systematic literature review and searched PubMed, the Cochrane database, andClinicalTrials.gov from January, 1995, with keywords including "Castleman's disease" and "giant lymph node hyperplasia". Inclusion criteria were pathology-confirmed Castleman's disease in multiple nodes and minimum clinical and treatment information on individual patients. Patients with HHV8 or HIV infection or diseases known to cause Castleman-like histopathology were excluded. Findings: Our search identified 626 (33%) patients with HHV8-negative multicentric Castleman's disease from 1923 cases of multicentric Castleman's disease. 128 patients with idiopathic multicentric Castleman's disease met all inclusion criteria for the systematic review. Furthermore, aggregated data for 127 patients with idiopathic multicentric Castleman's disease were presented from clinical trials, which were excluded from primary analyses because patient-level data were not available. Clinical features of idiopathic multicentric Castleman's disease included multicentric lymphadenopathy (128/128), anaemia (79/91), elevated C-reactive protein (65/79), hypergammaglobulinaemia (63/82), hypoalbuminaemia (57/63), elevated interleukin 6 (57/63), hepatomegaly or splenomegaly (52/67), fever (33/64), oedema, ascites, anasarca, or a combination (29/37), elevated soluble interleukin 2 receptor (20/21), and elevated VEGF (16/20). First-line treatments for idiopathic multicentric Castleman's disease included corticosteroids (47/128 [37%]), cytotoxic chemotherapy (47/128 [37%]), and anti-interleukin 6 therapy (11/128 [9%]). 49 (42%) of 116 patients failed first-line therapy, 2-year survival was 88% (95% CI 81–95; 114 total patients, 12 events, 36 censored), and 27 (22%) of 121 patients died by the end of their observed follow-up (median 29 months [IQR 12–50]). 24 (19%) of 128 patients with idiopathic multicentric Castleman's disease had a diagnosis of a separate malignant disease, significantly higher than the frequency expected in age-matched controls (6%). Interpretation: Our systematic review provides comprehensive information about clinical features, treatment, and outcomes of idiopathic multicentric Castleman's disease, which accounts for at least 33% of all cases of multicentric Castleman's disease. Our findings will assist with prompt recognition, diagnostic criteria development, and effective management of the disease. Funding: None.